New insights into interactions between the nucleotide‐binding domain of CFTR and keratin 8. (February 2017) - Premchandar, Aiswarya; Kupniewska, Anna; Bonna, Arkadiusz; Faure, Grazyna; Fraczyk, Tomasz; Roldan, Ariel; Hoffmann, Brice; Faria da Cunha, Mélanie; Herrmann, Harald; Lukacs, Gergely L.; Edelman, Aleksander; Dadlez, Michał
Abstract: The intermediate filament protein keratin 8 (K8) interacts with the nucleotide‐binding domain 1 (NBD1) of the cystic fibrosis (CF) transmembrane regulator (CFTR) with phenylalanine 508 deletion (ΔF508), and this interaction hampers the biogenesis of functional ΔF508‐CFTR and its insertion into the plasma membrane. Interruption of this interaction may constitute a new therapeutic target for CF patients bearing the ΔF508 mutation. Here, we aimed to determine the binding surface between these two proteins, to facilitate the design of the interaction inhibitors. To identify the NBD1 fragments perturbed by the ΔF508 mutation, we used hydrogen–deuterium exchange coupled with mass spectrometry (HDX‐MS) on recombinant wild‐type (wt) NBD1 and ΔF508‐NBD1 of CFTR. We then performed the same analysis in the presence of a peptide from the K8 head domain, and extended this investigation using bioinformatics procedures and surface plasmon resonance, which revealed regions affected by the peptide binding in both wt‐NBD1 and ΔF508‐NBD1. Finally, we performed HDX‐MS analysis of the NBD1 molecules and full‐length K8, revealing hydrogen‐bonding network changes accompanying complex formation. In conclusion, we have localized a region in the head segment of K8 that participates in its binding to NBD1. Our data also confirm the stronger binding of K8 to ΔF508‐NBD1, which is supported by an additional binding site located in the vicinity of the ΔF508 mutation in NBD1.